Pengaruh Fitur Layanan, Keamanan dan Kemudahan Terhadap Kepuasan Pengguna E-Wallet DANA Pada Mahasiswa Universitas Hindu Indonesia: Studi Kasus Pada Mahasiswa Fakultas Ekonomi Bisnis & Pariwisata Angkatan 2021 Universitas Hindu Indonesia Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
In enhancing user satisfaction, there are influencing factors such as service features, security, and ease of use. Service features refer to a product functioning with distinct characteristics. Security involves how we can prevent fraud. Ease of use refers to the level of user expectations regarding the effort required to use a system. The purpose of this study is to determine the effect of service features, security, and ease of use on user satisfaction both partially and simultaneously. The research was conducted on students of FEBP UNHI. The population of this study consisted of 2021 cohort students who use the DANA e-wallet, totaling 100 individuals. The sampling method used was total sampling, resulting in a sample of 100 people. Data collection methods included interviews, documentation, and questionnaires measured using a Likert scale. The analysis technique used was multiple linear regression. The results show that service features, security, and ease of use have a positive and significant partial effect on customer satisfaction. Furthermore, service features, security, and ease of use simultaneously have a positive and significant effect on user satisfaction. The recommendation given is to improve service features, understand the importance of security, and implement good ease of use practices so that user satisfaction continues to increase.